GAMBARAN PERENCANAAN, PERMINTAAN, DAN PENERIMAAN OBAT DI PUSKESMAS BANJARBARU UTARA TAHUN 2022 - Wahyuni, Amaliyah; Fatimatuzzahra, Fatimatuzzahra; Narulita, Feni (Jurnal Insan Farmasi Indonesia, 2023)
Drug management at the Community Health Center is an important indicator of the quality of pharmaceutical services because it determines the success of Community Health Center management. Drug management activities aim to ensure that drugs can be managed optimally. This type of research is non-experimental with a cross sectional research design using an observation sheet from retrospective data for 2022 which was carried out in February – May 2023. The population and sample are planning, demand and acceptance in the 2022 period. Secondary data processing for this research sheet Drug Needs Plan (RKO) and LPLPO for 2022. The results of the research were that the suitability of planning with the Community Health Center Formulary was 85.43% of the 103 planned drug items, there were 88 items that were appropriate and 15 items were inappropriate, the suitability of planning with demand was 4.85% of the 103 items that were planned, there were 5 items that were inappropriate. appropriate and 98 items that are not appropriate and the conformity of requests with acceptance is 3.60% of the 139 items requested there are 5 items that are appropriate and 134 items that are not appropriate.